ІНШОМОВНА КОМУНІКАТИВНА КОМПЕТЕНЦІЯ ВЧИТЕЛЯ ІНОЗЕМНИХ МОВ В КОНТЕКСТІ ПРОЦЕСУ ЄВРОІНТЕГРАЦІЇ УКРАЇНИ (Педагогіка вищої та середньої школи, 2008)
In the paper foreign language communicative competence of the teachers of foreign languages is discussed as a factor of success of Ukrainian integration into European educational sphere. The conditions of improvement of foreign language communicative competence developing process is presented in the system of in-service education.